Are the goals set by the millennium declaration and the programme of action of the international conference on population and development within reach by 2015? - Mercedes B. Concepcion (Asia-Pacific Population Journal, 2009)
It is now mid-2008, just seven years away from 2015, the target year for the realization of the International Conference on Population and Development (ICPD) Programme of Ac tion and the eight Millennium De velopment Goals.